Addressing the Practice of Safety Management in Halal Industry - An Overview and A Step Towards Sustainable Cooperation - Azizan, Ramli; Mohamad Ezuan, Abdul Jalil (Penerbit Universiti Malaysia Pahang, 2017)
Global demands of halal products are expected to increase in near future. Hence, Malaysia has taken proactive actions to realize its aspiration in becoming a champion of global halal hub. However, this development has also brought along impact on safety level for halal industry’s workers and neighborhood. Thus, the purpose of this paper is to provide an overview of safety management in halal industry and obtains halal player’s opinion towards cooperative safety management. The research method involved analysis on current state of safety management practice in halal industry and survey. These methods are not mutually exclusive approaches but they are complimentary. The results shown that both dominance (government-to-halal industry) and individual approaches (exclusively move as an individual) aim to establish mutual cooperation between authority and halal industry in fostering a safety culture. In addition, the findings also shown that the initial development of cooperative safety management is noteworthy but yet, this approach requires further in-depth study.